Four Flows theory and materiality: ISIL's use of material resources in its communicative constitution. Issue 3 (3rd July 2018) - Bruscella, Jacqueline S.; Bisel, Ryan S.
ABSTRACT: This paper extends Four Flows theory by showing how its agency-related assumptions can explain the role played by materials in the communicative constitution of organizations (CCO). Analysis of Dabiq – the propaganda periodical of ISIL (Islamic State of Iraq and the Levant) – illustrates how members of the complex organization engaged in activity coordination to position the organization through communication strategies such as instantiation, cooptation, and intertextual allusions. These institutional positioning strategies are themselves partially material, and we show how they function together with still other material resources as part-whole appeals in which the material part is projected to represent the whole of the organization's image and meaning across time and space. Each part-whole appeal is predicated on how the organization attributes meaning to its material resources. Implications for CCO theory are included.